Sulfated Cyclocarya paliurus polysaccharides exert immunomodulatory potential on macrophages via Toll-like receptor 4 mediated MAPK/NF-κB signaling pathways - Yue Yu; Haibin Zhu; Mingyue Shen; Qiang Yu; Yi Chen; Shiru Mo; Jianhua Xie (Food Science and Human Wellness)
The biological activity of plant polysaccharides can be enhanced by sulfated modification. In this study, the immunomodulatory effect of sulfated Cyclocarya paliurus polysaccharides (SCP3) on macrophages RAW264.7 and its potential molecular mechanism were investigated. Results showed that SCP3 at 25−100 μg/mL increased viability and improved phagocytosis of RAW264.7 cells. Meanwhile, SCP3 could activate mitogen-activated protein kinase (MAPK) and nuclear factor kappa B (NF-κB) signaling pathways, which increased the phosphorylation of Erk1/2, JNK, p38 and NF-κB p65, promoting secretion of cytokines tumor necrosis factor α (TNF-α), interleukin 6 (IL-6) and nitric oxide (NO) as well as the production of reactive oxygen species (ROS). In addition, Toll-like receptor 4 (TLR4) receptor inhibitors were able to block the production of NO and TNF-α by SCP3-stimulated macrophages. Based on Western blot analysis and validation using specific inhibitors against MAPK and NF-κB signaling pathways, the results demonstrated that SCP3 induced macrophages activation and enhanced TNF-α and NO production via TLR4-mediated MAPK and NF-κB pathways. In summary, SCP3 has significant immunomodulatory potential. The underlying molecular mechanism was that SCP3 activates macrophages via TLR4 receptors to promote ROS production, which in turn activates the downstream MAPK/NF-κB signaling pathway and then increases the secretion levels of cytokines and NO.